A amplitude de movimento de quadril está associada com a sensibilidade à dor em indivíduos com e sem osteoartrite de joelho? Um estudo transversal comparativo - Nóbrega, Isabela Lima (Universidade Federal de São Carlos, 2026)
Pain in knee osteoarthritis is mainly related to functional activities of daily living. Several factors are associated with the presence of pain in individuals with this condition, such as structural changes in the joint and also changes in pain processing due to repetitive load stimuli on the joint. The hip abductor muscles are related to overloads on the knee, for this reason the hip has been the subject of study for controlling disease progression and reducing pain. Biomechanical changes in the hip can also be observed, but the relationship between hip range of motion (ROM) and pain sensitivity in knee osteoarthritis still requires detailed investigation. Objective: To investigate the association between knee pain sensitivity and hip ROM in individuals with and without knee osteoarthritis. Secondarily, the association between ROM and muscle torque of hip rotations; the comparison of ROM between individuals with and without knee osteoarthritis, as well as the correlation between ROM, physical function and pain catastrophizing. This is a cross-sectional study with 26 individuals with osteoarthritis and 12 control individuals of similar height. Pain sensitivity was assessed using Quantitative Sensory Tests (QST), and hip ROM was measured using a digital inclinometer. Muscle torque was also assessed using an isokinetic dynamometer, and catastrophizing was measured using the Catastrophic Thinking Scale. Multiple linear regression was performed for the main objective; Student's t-test for independent samples was used to compare means, and Spearman's rank correlation coefficient was used. Analyses were performed using Rstudio, and the significance level adopted was p < 0.05. Multiple linear regression analysis revealed a significant interaction between the range of motion (ROM) of total hip rotation and the group (with and without osteoarthritis) in predicting pressure pain thresholds (PPT) in the knee (R²adj = 0.372; β = -0.11; p = 0.039). In the knee osteoarthritis group (GOA), it was found that greater ranges of motion were associated with lower pain thresholds (greater sensitivity), while the control group showed an inverse relationship. A significant negative correlation was found between hip rotation ROM and pain catastrophizing (ρ = -0.37; p = 0.02), indicating that lower levels of mobility are associated with a higher score on the catastrophizing scale (PCS), which also showed moderate to strong correlations with worse performance in physical function tests (ρ between 0.42 and -0.75; p < 0.01), explaining significant variations in muscle torque (R²addj between 0.27 and 0.46).
Is hip range of motion associated with pain sensitivity in individuals with and without knee osteoarthritis? A comparative cross-sectional study
Keywords: Testes sensoriais quantitativos; Biomecânica; Função física; Força muscular; Dor musculosquelética; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar